The potential role of pharmacogenomics and biotransformation in hypersensitivity reactions to paracetamol. Issue 4 (August 2018) - Agúndez, José A.G.; Gómez-Tabales, Javier; Ruano, Francisco; García-Martin, Elena
Abstract : Purpose of review: The aim of the present review is to discuss recent advances supporting a role of paracetamol metabolism in hypersensitivity reactions to this drug. Recent findings: Recent developments in the identification of novel paracetamol metabolites, as well as in allele frequencies and functional effects of genetic variation leading to the bioavailablity of reactive paracetamol metabolites, have led to the identification of potential pharmacogenomic and metabolomic targets in studies seeking mechanisms involved in hypersensitivity reactions caused by this drug. Particularly relevant are identification of araquidonate metabolites, identification of specific-binding sequences for reactive paracetamol metabolite-protein adducts, and studies on the frequencies and the functional impact of duplication or multiduplication of genes involved in the formation of reactive metabolites, as well as complete gene deletion or deleterious mutations in genes involved in the detoxification of paracetamol reactive metabolites. In addition, recent evidence points to sex, ethnic origin and age as relevant factors in the production of reactive paracetamol metabolites. Summary: High inter-individual variability in the production of reactive paracetamol metabolites exists, and factors leading to increased bioavailability of reactive paracetamol metabolites are being uncovered. Additional research is required to link these factors to paracetamol-induced hypersensitivity reactions.